Prostate cancer with metastases to the kidney: a rare manifestation of a common disease. (1st August 2013) - Khan, Fahd; Mahmalji, Wasim; Sriprasad, Seshadri; Madaan, Sanjeev
Abstract : A 66-year-old Caucasian man with a background of prostate cancer presented with a progressive history of nausea, reduced appetite, shortness of breath and a distended abdomen. Radiological imaging revealed a left-sided renal mass and gross ascites suggestive of metastatic renal cell carcinoma (RCC). Subsequent histological examination and immunostaining of renal mass biopsy revealed features characteristic of metastatic moderately differentiated to a focally poorly differentiated, large duct type of prostatic adenocarcinoma.